Improving the Tourism Management of Grandpa Land Trikora Beach, Bintan - Kamaruzaman; Yonantha, Ferri; Aqmal, Romi; Khairun Nida, Adelia; Juniyanti, Lilis; Sari, Nur Evita; Kencana, Pamela Kenia (Advances in Humanities and Contemporary Studies, 2022)
Grandpa Land Trikora Beach is a new spot among the Trikora beaches. It was firstly open in 2016 and publically opened by August 2021. It is a very potential tourism object in Bintan, Kepulauan Riau. Thus, the its management is highly needed to increase its potentials. The better management, the better improvement will be. This research was carried out with a qualitative descriptive approach. The data were collected through in-depth interview and research object observation. Some recommendations are suggested by the researcher after doing the research as the efforts to increase the potencies of Grandpa Land Trikora Beach. Management should increase its performance by improving the service and do promotion with more massively by using media social with more platforms and frequently updating the news of Grandpa Land Trikora Beach to the people.